2010
DOI: 10.1159/000318187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Health-Related Quality of Life in Patients with Prostate Cancer after Treatment with Radical Retropubic Prostatectomy and Permanent Prostate Brachytherapy

Abstract: Aim: The aims of this study were to evaluate the health-related quality of life (HRQOL) and make the treatment decision less difficult. Methods: Between 2007 and 2009 radical retropubic prostatectomy (RRP) was performed in 96 patients and permanent prostate brachytherapy (PPB) in 88 patients at our hospital. The general and disease-specific HRQOL was measured using two instruments, the Medical Outcome Study 8-Item Short-Form Health Survey (SF-8) and the expanded prostate index composite (EPIC). Results: Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2010
2010
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 45 publications
0
7
0
3
Order By: Relevance
“…However, lower educational levels, older ages of the spouse, higher incomes and lower tumour stages have been reported to be associated with higher QOL (Song et al , ). Patients who received prostatectomy have been reported to have lower QOL than those treated with radiation therapy or hormone therapy (Krahn et al , ; Takizawa et al , ; Dragicevic et al , ); thus, efforts should be made to enhance the QOL of patients. Based on these findings, we propose that the relevant factors influencing the QOL of patients be identified and an intervention programme be developed in order to enhance the QOL of this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…However, lower educational levels, older ages of the spouse, higher incomes and lower tumour stages have been reported to be associated with higher QOL (Song et al , ). Patients who received prostatectomy have been reported to have lower QOL than those treated with radiation therapy or hormone therapy (Krahn et al , ; Takizawa et al , ; Dragicevic et al , ); thus, efforts should be made to enhance the QOL of patients. Based on these findings, we propose that the relevant factors influencing the QOL of patients be identified and an intervention programme be developed in order to enhance the QOL of this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Dragićević et al . [6] evaluated HRQOL in patients after treatment with ORRP and prostate brachytherapy (BT). They measured general and disease‐specific HRQOL and found that there were significant differences in all scores except for general health in the 1st month after treatment.…”
Section: Choice Of Treatmentmentioning
confidence: 99%
“…Quanto ao domínio da qualidade de vida direcionada à função sexual dos participantes, a literatura aponta resultados similares no mesmo período (VAN TOL-GEERDINK et al, 2013). Contudo, em relação aos escores da subescala de função sexual a média apresentada pelos participantes (M = 54,43; DP = 22,90) foi superior aos resultados médios apresentados na literatura (M = 28,3; DP = 21,5) (DRAGICEVIC et al, 2010). Por outo lado, em relação ao incômodo sexual apresentado pelos participantes nesta pesquisa (M = 63,07; DP = 30,13) os resultados divergiram do apresentado pela literatura, os quais foram superiores (M = 85,1; DP = 20,5) (DRAGICEVIC et al, 2010).…”
Section: Dados Clínicos E Psicológicos Do Pré-operatório (T0)unclassified
“…Em relação ao domínio de hábito intestinal (M= 88,6; DP = 9,97), quando avaliados a função intestinal e incômodo intestinal os participantes apresentaram dados (Tabela 13) similares ao da literatura (M = 85,7; DP = 13,7) para função intestinal (M = 94,5; DP = 7,2) para incômodo intestinal, respectivamente) (DRAGICEVIC et al, 2010).…”
Section: Dados Clínicos E Psicológicos Do Pós-operatório (T1)unclassified
See 1 more Smart Citation